Judicial proceedings within a reasonable time: European experience and Ukrainian realities - Olha Kubarieva (Юридичний часопис Національної академії внутрішніх справ, 2023)
The study addresses the increasing number of appeals against Ukraine to the European Court of Human Rights, most of which highlight violations of the right to a fair trial within a reasonable time. The purpose of the study is to clarify the content of procedural time limits for criminal proceedings and conduct a comparative analysis of legislative approaches in European countries to regulate the mentioned issues. The methodological basis of the study is the principle of consistency, within which the methods of comparative and system-structural analysis, synthesis, logical-legal, statistical and heuristic methods were used. The study explores the existing legislative shortcomings related to ensuring reasonable time frames for criminal justice and investigates problematic issues for its improvement. It is noted that the previous criminal procedural legislation did not declare the principle of reasonable time for criminal proceedings and lacked means for its enforcement. The necessity of ensuring judicial proceedings within a reasonable time is declared in Articles 21, 28, and 318 of the Criminal Procedure Code of Ukraine. Emphasis is placed on the interconnection between reasonable time and the continuous nature of judicial proceedings, considering the proceedings as a whole to ensure their prompt conclusion. The absence of procedural safeguards in Ukrainian legislation against unjustified delays in the trial of criminal proceedings in the first-instance court is highlighted. The study analyses the legal provisions of national criminal procedural legislation and the regulatory framework of European countries (Bulgaria, Estonia, Italy, Croatia). The necessity of strengthening guarantees for timely justice is substantiated. A set of measures to ensure the time parameters of the trial in the first-instance court is proposed, encompassing both organisational and procedural guarantees. The need for establishing a justified legislative procedure for expediting judicial proceedings in case of violations of the accusedʼs and the victimʼs right to a reasonable time for conducting criminal proceedings is justified. The practical value of the study lies in the fact that its results and recommendations can be utilised for the reform of the judicial system